Access to assisted reproduction in Latin America: recent trends and future perspectives. Issue 1 (December 2017) - Horton, Marcos
Abstract : Assisted Reproduction is now an established technology to treat infertility. New technological and biomedical advances, added to changing sociocultural views in modern societies have broaden the scope of Assisted Reproduction Treatment, so prospective parents today include conventional infertility couples, single women, or men, gay/lesbian individuals, HIV serodiscordant couples, or carriers of genetic conditions. In addition, younger patients can decide on gamete storage for later use, due to medical or social reasons. The situation in Latin America varies significantly in different countries, despite sharing a common cultural and religious background, but those countries with recent sanctions of IVF laws, regulations, or other legislation related to civil rights, gender identity, or same sex marriage show better access of its population to Assisted Reproduction Treatment.